Do liars really remember what they lied upon? The impact of fabrication on memory. Issue 8 (14th September 2021) - Battista, Fabiana; Mangiulli, Ivan; Riesthuis, Paul; Curci, Antonietta; Otgaar, Henry
ABSTRACT: The present experiment aimed to examine how fabrication can affect memory. In particular, we examined whether different types of fabrication can lead to different mnemonic effects. A sample of 159 participants watched a video of a robbery and subsequently answered some questions about it. Participants were divided into three conditions: one group was instructed to tell the truth (i.e., truth-telling group), while the other two groups were instructed to lie either by partially distorting details (i.e., distortion group) or by completely making up wrong details of the event seen in the video (i.e., fabrication group). Two days later, participants completed a final memory test where they honestly answered recognition and recall questions concerning: (i) memory for the video and (ii) memory for having discussed details during the interview. Results showed that different types of fabrication affect liars' memory differently. Fabricators reported an undermining of memory for the event, whereas those who partially distorted details reported a higher impairment for the interview. Our findings showed that the effects of lying on liars' memory might be determined by the cognitive resources required to lie.